Sosialisasi penggunaan Permainan Edukatif dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris Siswa Kelas 2 Sekolah Dasar 01 Pandak Bandung, Tabanan - I Wayan Suadnyana; Dika Pranadwipa Koeswiryono; Putu Sri Darmayanti; Ni Made Sri Rahayu; Utik Kuntariati (Yayasan Kajian Riset dan Pengembangan RADISI, 2026)
English language learning at the elementary school level, particularly in vocabulary acquisition, still faces several challenges, including low student motivation and the use of conventional, less interactive teaching methods. This community service program aims to improve the English vocabulary mastery of second-grade elementary school students through the implementation of educational game-based learning. The method was carried out through five stages: preparation, socialization, instructional implementation, monitoring and evaluation, and reflection and follow-up. The core activities involved vocabulary instruction using visual media and educational games such as bingo, flashcard games, and guessing games. The results indicate a significant improvement in students’ vocabulary mastery, increasing from an average of 5–10 words to 15–20 words used actively. Additionally, there was an increase in student engagement and learning motivation, as well as improved teacher competence in applying interactive teaching methods. Therefore, educational game-based learning is proven to be effective in enhancing the quality of English vocabulary instruction at the elementary school level.